Modelling cyber resilience in a water treatment and distribution system. (October 2022) - Patriarca, Riccardo; Simone, Francesco; Di Gravio, Giulio
Highlights: A simulation-based methodology to assess cyber resilience in water supply systems. A joint resilience analysis of a water treatment plant and its distribution network. An integrated MATLAB/EPANET model based on Monte Carlo simulation. Four metrics to assess attack's impact in terms of water quality and quantity. A statistical analysis of cyber resilience indicators to support decision-making. Abstract: Considering the increasing introduction of cyber-physical systems in modern industrial plants, the analysis of systems' performance pushes for developing a cyber resilience perspective to complement a traditional physical resilience assessment. This point of view becomes central for critical infrastructures, considering the potential societal and economic consequences a disruption may have. This work provides a cyber-resilience simulation-based assessment for a seawater desalination plant and its connected distribution system. For this purpose, a digital twin has been developed. It integrates a MATLAB/Simulink model of the reverse osmosis treatment plant with a georeferenced water distribution network designed in EPANET. Four stochastic cyber resilience metrics have been proposed and computed to assess the impact of a successful replay cyber attack. The results exemplify the benefits of cyber-physical simulations to understand the behavior of modern water treatment plants, to identify system's criticalities, and eventually to support decision making by identifying hotspots and prioritizing mitigating actions.